Is it sustainable? A comparison of student and tutor online time across three distance-learning courses - Tina Wilson; Denise Whitelock (Association for Learning Technology, 1998)
Computer Mediated Communication (CMC) is a useful pedagogical tool. Mason (1989a) states that it has proved to be 'a life-line to help, information, contact and exchange' for students. Thomas (1989) discusses the benefits of CMC from the tutor and course team perspectives. However, Rumble (1989) discusses the difficulties of costing the introduction of CMC into a course. If more and more distance-learning institutions are going to adopt this medium, it is important to evaluate for all concerned the time required for this type of participation.